Iowa Birdline update, January 20, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for January 20, 1989. Highlights include continued sightings of a Slaty-backed Gull. Included with this document is a script for the Iowa Birdline update for March 6, 1989. Highlights include a flock of Mountain Bluebirds. Epson - sheet feed/flatbed